'A woman before a person': teachers navigating gender roles during international experiences. (20th October 2021) - Mitchem, Melissa C.
ABSTRACT: While studies have explored the affordances and limitations of teachers' international experiences in developing their critical global perspectives, few have attempted to understand what teachers observe about gender roles and expectations during their time abroad. In this study, I interpret the narratives of three U.S. women teachers who participated in educative international experiences through the lens of transnational feminism. My analysis reveals the similarities and differences across these women in their observations of gender norms and expectations. Their narratives suggest the potential of focusing on gender during an international experience for teacher educators seeking to develop teachers' critical global perspectives.